THE EFFECT OF OWNERSHIP STRUCTURE, COMPANY SIZES AND CORPORATE CHARACTERISTICS OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES IN COMPANIES MANUFACTURE LISTED IN INDONESIA STOCK EXCHANGE - Rafika, Mulya (LPPM Universitas Labuhanbatu, 2020)
Corporate Social Responsibility (CSR) is a concept in an organization or company which has various responsibilities towards employees, shareholders, consumers, society, and the surrounding environment. Therefore CSR is very closely related to sustainable development that companies are required not only to concentrate on profits, but also to consider all production risks which may occur to the environment and surrounding communities at short and long term. The purpose of this study was to determine whether the ownership structure,the size of company and the characteristics of company influence the disclosure of corporate social responsibility in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study was 17 companies during the 2014-2016 period so that it became 51 research data using purposive sampling. The analysis technique used is multiple linear regression. The results showed that ownership structure has a negative and a significant influence on corporate social responsibility, the size of the company has a significant positive influence on corporate social responsibility has a significant positive influence on corporate social responsibility and the characteristics of the company have a positive and insignificant influence on corporate social responsibility.